2009
DOI: 10.1159/000232937
|View full text |Cite
|
Sign up to set email alerts
|

Association between Markers of Inflammation, Fibrosis and Hypervolemia in Peritoneal Dialysis Patients

Abstract: Background/Aim: Volume expansion in peritoneal dialysis (PD) patients is associated with left ventricular hypertrophy. The link between inflammation and hypervolemia has not been extensively studied. The aim of this study was to determine if an association exists between hypervolemia and markers of inflammation in PD patients. Methods: In this cross-sectional study of 22 prevalent PD patients, volume was determined by bioelectrical impedance analysis. Serum and peritoneal effluent interleukin-6 (IL-6) and peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 52 publications
2
19
0
Order By: Relevance
“…Similarly, malnutrition may also contribute to an elevated ratio of extracellular water to total body water as a result of loss of fat weight (17). These findings are in keeping with recent reports of raised BNP being associated with inflammation (7,12) and overhydration (18). However, we did not find any association between CRP and log NT-proBNP, in keeping with other reports (18).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similarly, malnutrition may also contribute to an elevated ratio of extracellular water to total body water as a result of loss of fat weight (17). These findings are in keeping with recent reports of raised BNP being associated with inflammation (7,12) and overhydration (18). However, we did not find any association between CRP and log NT-proBNP, in keeping with other reports (18).…”
Section: Discussionsupporting
confidence: 92%
“…These findings are in keeping with recent reports of raised BNP being associated with inflammation (7,12) and overhydration (18). However, we did not find any association between CRP and log NT-proBNP, in keeping with other reports (18). One previous report found a correlation between log NTproBNP and CRP, but interestingly in that study a raised CRP did not predict a raised log NT-proBNP, and their median CRP values were higher than in our cohort (12).…”
Section: Discussionsupporting
confidence: 91%
“…[2][3][4][5] There is accumulating evidence that overexpression of transforming growth factor b1 (TGF-b1) plays a key role in the observed long-term changes in peritoneal function [6][7][8][9] and is correlated with worse PD outcomes. 9,10 Experiments showed that inhibition of TGF-b1 bioactivity can attenuate extracellular matrix (ECM) deposition and the progression of tissue fibrosis in different experimental models. [11][12][13] Nevertheless, TGF-b1 plays a complicated and controversial role in an immune regulation due to its highly pleiotropic properties and the presence of TGF-b1 receptors on most cell types.…”
Section: Introductionmentioning
confidence: 99%
“…TGF-β1 activates Smad2 and Smad3, which consequently induces a molecular transition that results in the downregulation of the intracellular adhesion molecule E-cadherin and upregulation of mesenchymal-associated molecules, such as Snail, α-SMA, and fibronectin. Clinical studies have shown that the levels of TGF-β1 detected in the PD fluid correlated with the risk of technical failure in the PD patients 32, 33. Furthermore, overexpression of TGF-β1 by the transfection of adenovirus vectors into the peritoneal cavity led to peritoneal fibrosis, angiogenesis, and ultrafiltration failure in an animal model of the PD 34 .…”
Section: Discussionmentioning
confidence: 99%